Impact of SARS-CoV-2 on Male Reproductive Health: A Review of the Literature on Male Reproductive Involvement in COVID-19 - He, Weihang; Liu, Xiaoqiang; Feng, Liang; Xiong, Situ; Li, Yulei; Chen, Luyao; Li, Yu; Wang, Gongxian; Li, Dongshui; Fu, Bin (Frontiers in Medicine, 2020)
Coronavirus Disease 2019 (COVID-19) has constituted a pandemic. Epidemiological results show that men are susceptible to infection and have a high mortality rate of COVID-19. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the pathogen of COVID-19, which is transmitted through respiratory droplets, direct and indirect contact. Genomic analysis has shown that SARS-CoV-2 is 79% identical to SARS-CoV, and both use angiotensin-converting enzyme 2 (ACE2) as the receptor for invading cells. Transmembrane serine protease 2 (TMPRSS2) can enhance ACE2-mediated virus entry. However, SARS-CoV-2 has a high affinity with human ACE2, and the consequences are more serious than other coronaviruses. ACE2 acts as a “gate” for viruses to invade cells and is closely related to the clinical manifestations of COVID-19. Studies have found that ACE2 and TMPRSS2 are expressed in the testis and male reproductive tract and are regulated by testosterone. This review summarizes the gender differences in the pathogenesis and clinical manifestations of COVID-19 and proposes the possible mechanism of orchitis caused by SARS-CoV-2 and the potential transmission route of the virus. In the context of the pandemic, these data will improve understanding on the poor clinical outcomes of male patients with COVID-19 and the design of new strategies to prevent and treat SARS-CoV-2 infection.